Análise sobre o processo de gestão de documentos no arquivo central da Universidade Federal do Pará - RIBEIRO, Sabrina Letícia Pereira (2019)
The present undergraduate thesis aims to ponder upon the following theme: Archival science — the process of curating archives at Central Archive of the Federal University of Pará - UFPA. Our main objective is to verify whether the curation of archives at UFPA’s Archive Center is adequate or not. More specifically, it is intended to delineate the processes of curatorship employed at the aforementioned department and outline its main features. The methodology is based on qualitative and field researches. The results and discussions were derived from the analysis of the answers obtained from interviews.